Determination of Serum Zinc, Manganese, Copper and Cobalt Traces In Type Two Diabetic Patients in Sulaimaniyah City Using ICP Technique - Abdullah, A. M.; Salh, D. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Direct determination of trace metals Zn, Mn, Cu and Co were performed in serum blood samples of two groups diabetic patient type 2 and non diabetes by ICP spectrometric method. Results show the low levels of these elements Zn, Mn and Co while high level of Cu detected compared with non diabetes according to these results good evidence can be made to control these levels through a special diet containing these metals.